2017
DOI: 10.25046/aj0203188
|View full text |Cite
|
Sign up to set email alerts
|

Source Code Vulnerabilities in IoT Software Systems

Abstract: An empirical study that examines the usage of known vulnerable statements in software systems developed in C/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Few researchers have suggested medium and long-range low-power wireless technologies like long range (LoRa) communication, Zigbee, BLE, and WIFI [11][12][13] On the other In V2X, vehicles share their instantaneous information such as their speed, coordinates, and acceleration to other vehicles and necessary infrastructure [7]. A few of the major challenges of V2X communication include time criticality, latency intolerance, security, and privacy [8][9][10]. Building a reliable architecture and choosing the right communication technology is vital for addressing these challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Few researchers have suggested medium and long-range low-power wireless technologies like long range (LoRa) communication, Zigbee, BLE, and WIFI [11][12][13] On the other In V2X, vehicles share their instantaneous information such as their speed, coordinates, and acceleration to other vehicles and necessary infrastructure [7]. A few of the major challenges of V2X communication include time criticality, latency intolerance, security, and privacy [8][9][10]. Building a reliable architecture and choosing the right communication technology is vital for addressing these challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Alnaeli et al [ 43 ] extended their previous work [ 42 ] to empirically examine the vulnerabilities of eighteen open-source IoT software systems, all of which were specifically written in C/C++ for IoT architectures. They found that usage of unsafe functions was still common among the selected systems, and developers were not working to improve the problems that were still present in the selected systems.…”
Section: Related Workmentioning
confidence: 99%
“…Both Alnaeli et al [ 42 , 43 ] and McBride et al [ 44 ] presented different results for the total number of unsafe functions, since different static analysis tools were used. Both of the studies used the term unsafe function to describe vulnerable commands and statements in terms of functions written by C/C++ programming language.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations